2014
DOI: 10.1039/c3fo60641d
|View full text |Cite
|
Sign up to set email alerts
|

N-3 PUFA increase bioavailability and function of endothelial progenitor cells

Abstract: Our findings support the case of a beneficiary role played by n-3 PUFA in EPC function and bioavailability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 42 publications
(49 reference statements)
0
19
0
Order By: Relevance
“…EPC levels were assessed by cytofluorimetric analysis and identified as cells co-expressing CD34, CD133, and Kinase insert Domain Receptor (KDR) surface antigens as previously described [ 42 , 43 , 44 , 45 ]. Briefly, 300 µL of blood collected in EDTA were stained with 15 μL fluorescein isothiocyanate (FITC)-conjugated anti-human CD34 monoclonal antibody (mAb) (Becton Dickinson Biosciences, Franklin Lakes, NJ, USA), 20 μL phycoerythrin (PE)-conjugated anti-human KDR mAb (R&D Systems, Minneapolis, MN, USA) and 20 µL allophycocyanin (APC)-conjugated anti-human CD133 mAb (Miltenyi Biotec, San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…EPC levels were assessed by cytofluorimetric analysis and identified as cells co-expressing CD34, CD133, and Kinase insert Domain Receptor (KDR) surface antigens as previously described [ 42 , 43 , 44 , 45 ]. Briefly, 300 µL of blood collected in EDTA were stained with 15 μL fluorescein isothiocyanate (FITC)-conjugated anti-human CD34 monoclonal antibody (mAb) (Becton Dickinson Biosciences, Franklin Lakes, NJ, USA), 20 μL phycoerythrin (PE)-conjugated anti-human KDR mAb (R&D Systems, Minneapolis, MN, USA) and 20 µL allophycocyanin (APC)-conjugated anti-human CD133 mAb (Miltenyi Biotec, San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…26 Angiogenin can also promote EPC proliferation and colony formation. 27 In terms of the downregulated cytokines, IL-8, 28 MCP-1 29 and MIP-1β 30 are pro-inflammatory factors and can exert adverse effects on EPC or endothelial cell biology. Moreover, TNF-α can impair EPC proliferation, migration, adhesion capacity, and vasculogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…2 For example, research developed by our group showed that the echinoderm Marthasterias glacialis (spiny sea-star) contains a big amount of fatty acids, being an interesting source of anti-inammatory molecules. 5,6 As vegetable oils do not contain long-chain PUFA and the conversion of C 18 PUFA to eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in the human body is inefficient, there has been considerable interest in nding new marine sources for these fatty acids. 4 The u-3 PUFA provide a myriad of health benets, including reduction of cardiovascular diseases and anti-carcinogenic activities.…”
Section: Introductionmentioning
confidence: 99%